Analisis Perencanaan Sumber Daya Manusia dalam Peningkatan Efektivitas Organisasi pada Lembaga Pendidikan - Imron I; Mutiara Sofa (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the role of human resource planning (HRP) in enhancing organizational effectiveness in educational institutions through a qualitative library research approach. Human resource planning is understood as a strategic process that ensures the availability of competent teaching and non-teaching personnel who meet organizational needs and align with institutional goals. The data were obtained from scholarly books, accredited journal articles, and policy documents related to human resource management in the educational context. The findings indicate that HRP includes several stages, such as workforce needs analysis, labor forecasting, competency mapping, and continuous professional development. Supporting factors include visionary leadership, a conducive organizational culture, and accurate data systems; while inhibiting factors involve budget limitations, competency gaps, and regulatory dynamics. The literature also shows that effective HRP directly contributes to organizational effectiveness by improving performance, enhancing the quality of educational services, and increasing resource management efficiency. This study emphasizes that HRP is a fundamental pillar in strengthening governance within educational institutions.